Servant leadership for the retention of millennial employees in private sectors: Mediating role of job satisfaction - Hassan M.M.; Jambulingam M.; Narayan E.A.L.; Alam M.N.; Islam M.S. (Inderscience Publishers, 2023)
The purpose of the study was to find out the effects of servant leadership on millennial employee retention in private sectors to combat the massive losses due to Generation Y turnover. All the stakeholders desire to have a lesser turnover to avoid losses, brain drain, and keep constant productivity. Millennial employees differ from their predecessors in terms of job-hopping. Although the enormous studies have been carried out in the western context, the problem of frequent millennial turnover remains unresolved. Moreover, study on impacts of servant leadership over millennial retention is perceived to be missing in non-western context. In this quantitative study, SMART PLS was employed for analysis. The result reveals that servant leadership got a significant positive relationship in millennial employees' retention. The mediating role of job satisfaction also found to be significant in this relationship. Finally, the study found to have implications for all stakeholders and future researchers. 2022 Inderscience Enterprises Ltd.. All rights reserved.